A revision of the tropical/temperate amphipod genus Dulichiella Stout, 1912, and the description of a new Atlantic genus Verdeia gen. nov. (Crustacea: Amphipoda: Melitidae) - Lowry, J. K.; Springthorpe, R. T. (Zootaxa, 2007)
The melitid amphipod genus Dulichiella Stout, 1912, is revised. Based on examination of type material or new material from near type localities, we redescribe D. anisochir (Krøyer, 1845) from Brazil, D. appendiculata (Say, 1818) from the south-eastern United States, D. australis (Haswell, 1879) from eastern Australia, D. cotesi (Giles, 1890) from the Andaman Islands, D. cuvettensis Appadoo & Myers, 2005 from Mauritius, D. fresnelii (Audouin, 1826) from the Red Sea, D. pacifica Lowry & Springthorpe, 2005 from Australasia and D. spinosa Stout, 1912 from California. Based on published illustrations and new material we describe six new species: D. guinea sp. nov. from western Africa; D. lecroyae sp. nov. from the south-eastern United States; D. oahu sp. nov. from Hawaii; D. terminos sp. nov. from south-eastern Mexico; D. tomioka sp. nov. from Japan and D. tulear sp. nov. from Madagascar. The new genus Verdeia is described for two established species, Melita grandimana Chevreux, 1908 from the Cape Verde Islands and Melita subchelata Schellenberg, 1925 from Namibia. We provide a key to the world species of these genera.